Comparative Effects of Whole Stevia Leaf and Rebaudioside A on Oxidative Stress in Male Obese Sprague Dawley Rats - Sadia Mubarak, Amna Faruqi, Bushra Riaz, Tallat Naureen, Ujala Ali, M. Irfan-ul-Akbar Yousufzai, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Obesity is a dilemma nowadays for increasing percentage of people worldwide. Obesity induced oxidative stress due to increased tissue lipid levels, threatened redox state of cell and increased free radical formation leads to tissue oxidative stress. Fatty liver disease is a very common disorder related with obesity resulting in storage of fat goblets in the liver tissues leading to altered redox state called oxidative stress. Aim: To relate the outcome of Stevia and Rebaudioside A on Oxidative stress (MDA, SOD) in Obese Sprague Dawley Rats. Place and duration of study: Physiology Department of Islamabad Medical and Dental College, Islamabad, in collaboration with National Institute of Health (NIH) from 1st January 2020 to 30th June 2022. Methodology: One hundred and twenty healthy male Sprague Dawley rats were included. The animals were divided randomly into four groups of 30 rats each by simple randomization technique. Group 1 was given normal diet while the other three groups were given high fat diet. Stevia leaves and Rebaudioside A (rebiana) were further added for six weeks in the diet of Group 3 and 4 respectively. All animals were sacrificed at the end of study. Results: High fat diet induced oxidative stress in obese group was restored to approximate normal values of SOD (0.001) and MDA (0.001) by treatment with stevia and rebiana both (0.899). Conclusion: Stevia and Rebiana both cause improvement of oxidative stress unrewarding of expensive extraction procedures. Keywords: Stevia rebaudiana, Rebaudioside A, Sprague Dawley rats, Oxidative stress, NAFLD